Methods of Improving Superconductive Fault Current Limiting Devices in Power Engineering - Hashimov, A. M.; Nayir, A.; Kazimov, S. A.; Bondyakov, A. S.; Hasanova, S. I. (Elektronika ir Elektrotechnika, 2013)
Superconducting fault current limiter is a fundamentally new type of device that has no direct analogue among the traditional electrical equipments. The basis of most of its variety, subject to intensive research in the world, is based on the principle of transition-temperature superconductors in the resistive (normal) condition when the current extended, flowing through the superconducting fault current limiter, above defined value. The problem of scaling on superconducting power of current-limiting transformer-type device has been investigated. Opportunities of increasing nominal power of such device based on experiments and calculations have been proposed. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.1441